Por um ensino de ciências biológicas vegano - Campos, Virginia de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This research of bibliographical revision presents a different view from the one traditionally used, of the animals by the Biological Sciences; thus reviewing the scientific backstage. It revisits the philosophy behind the mechanization in animal use and exploitation. In addition to this crucial point of the scientific treatment of animals, this study also shows how Biology can and should be directed to veganism and how the teaching of biology can contribute to the formation of antivivisseccionistas and biocentric students and teachers, in favor of life. By looking at the whole social structure - Moral, Ethics and Culture, by investing in the training of educators, promoting a humanitarian education, one can break the truculent foundations that support violence in its different forms

Esta pesquisa de revisão bibliográfica apresenta uma visão diferente da tradicionalmente utilizada dos animais pelas Ciências Biológicas; revendo assim os bastidores científicos. Revisita a filosofia por trás da mecanização no uso e na exploração animal. Além deste ponto crucial do trato científico aos animais, este estudo ainda apresenta como a Biologia pode ser dirigida ao veganismo e como que o ensino das Ciências Biológicas pode contribuir para a formação de educados(as) e educadores(as) antivivisseccionistas e biocêntricos, a favor da vida. Olhando para toda a estrutura social - Moral, Ética e Cultura -, investindo na formação de educadores, promovendo o exercício de uma educação humanitária, pode-se romper as bases truculentas que sustentam a violência em suas diversas formas
Keywords: Biologia - Estudo e ensino; Vegetarianismo; Experimentação animal